Reusable tourniquets for blood sampling as a source of multi-resistant organisms– a systematic review - Szymczyk, Julia; Månsson, Michelle; Mędrzycka-Dąbrowska, Wioletta (Frontiers in Public Health, 2023)
Introduction The use of reusable tourniquets is widespread around the world, and reports suggest they may be overused. Several studies have shown that reusable tourniquets can affect the spread of pathogens between patients. Based on available studies, this review aims to analyse the indirect transmission of antimicrobial-resistant pathogens present on blood collection tourniquets, which may spread infectious diseases between patients in daily clinical practice. Methods A systematic review of the literature was conducted according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) protocol guidelines. The contents of PubMed, EBSCO (electronic databases), and Scopus were screened. Keywords used in the search included: “tourniquet,” “cross infection,” “nosocomial infection,” “staphylococcus aureus,” “MRO,” “pathogen,” “infectious disease,” “anti-microbial,” or a combination of these using AND or OR operators. Finally, 13 publications were included. Data were analysed both descriptively and quantitatively by calculating a balanced average for specific synthesized data. Results The proportional observation based on the number sampled median was 77. The genus MRSA was the type of bacteria most commonly found: on 12% of all tested tourniquets. The amount of MRSA found on tourniquets was mean ± SD 14.6 ± 45.89. A review of studies also revealed the presence of coagulase-negative staphylococci, grew Bacillus, and Staphylococcus aureus. Conclusion Patient safety may be at risk due to elevated contamination rates of reusable tourniquets. The microorganisms responsible for this contamination include a variety of species, the most common being the genus Staphylococcus. For this reason, we recommend the use of disposable tourniquets.